2016
DOI: 10.3390/e18040144
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Quantum Interference in Document Relevance Judgement Discrepancy

Abstract: Quantum theory has been applied in a number of fields outside physics, e.g., cognitive science and information retrieval (IR). Recently, it has been shown that quantum theory can subsume various key IR models into a single mathematical formalism of Hilbert vector spaces. While a series of quantum-inspired IR models has been proposed, limited effort has been devoted to verify the existence of the quantum-like phenomenon in real users' information retrieval processes, from a real user study perspective. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 73 publications
1
30
0
1
Order By: Relevance
“…By conducting a between‐subject experiment, this study confirmed the partial existence of order effect and quantum interference on relevance judgment. The results are consistent with prior studies (Eisenberg & Barry, ; Wang et al, ). However, inconsistent with the findings from Wang and Huang (2004), we found that the order effect is also significant even when there are only two full‐texts to be assessed.…”
Section: Discussion and Conclusonsupporting
confidence: 93%
See 1 more Smart Citation
“…By conducting a between‐subject experiment, this study confirmed the partial existence of order effect and quantum interference on relevance judgment. The results are consistent with prior studies (Eisenberg & Barry, ; Wang et al, ). However, inconsistent with the findings from Wang and Huang (2004), we found that the order effect is also significant even when there are only two full‐texts to be assessed.…”
Section: Discussion and Conclusonsupporting
confidence: 93%
“…Comparing with the classical probability theory, the model based on quantum theory is more inclusive and has stronger explanatory power for both compatible and incompatible events by representing the vector spaces as orthogonal axes in a Hilbert space, rather than in the form of a set. (Uprety and Song, 2018; Wang et al, )…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, we observed an increasing interest toward the use of quantum formalism in non-microscopic domains [1][2][3][4]. The idea is that the powerful predictive properties of quantum mechanics, used for describing the behavior of microscopic phenomena, turn out to be particularly beneficial also in non-microscopic domains.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we will not enter into such features also in the present paper but we will limit ourselves to elaborate only upon specific questions. One example is given by the so called question of the order-effect that also recently has been represented in this journal by us (see as example, Wang et al, 2016 …”
Section: Introductionmentioning
confidence: 99%